Late Permian-Early Jurassic vertebrate tracks from patagonia: Biochronological inferences and relationships with southern african realms. - Díaz Martínez, Ignacio (2019)
Fil: Díaz Martínez, Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas (CONICET), Argentina.